Effect of ingesting a honey-sweetened beverage on soccer performance and exercise-induced cytokine response - Abbey, E. L.; Walberg Rankin, J. (International Journal of Sport Nutrition and Exercise Metabolism, 2009)
This study compared the effect of a honey-sweetened beverage with those of a commercial sports drink and a placebo on performance and inflammatory response to a 90-min soccer simulation. Methods: Ten experienced male soccer players randomly performed 3 trials (honey [H], sports drink [S], and placebo [P]), consuming the beverage before and during halftime for a total of 1.0 g/kg carbohydrate for H and S. Performance measures included 5 sets (T1-T5) of a high-intensity run and agility and ball-shooting tests followed by a final progressive shuttle-run (PSR) test to exhaustion. Blood samples were drawn pretest, posttest (B2), and 1 hr posttest (B3) for markers of inflammation, oxygen radical absorbance capacity (ORAC), and hormone response. Results: T2-T5 were significantly slower than T1 (p < .05), and a decrease in PSR time was observed from baseline (-22.9%) for all treatments. No significant effect of the interventions was observed for any performance measures. Plasma IL-1ra levels increased posttest for all treatments (65.5% S, 63.9% P, and 25.8% H), but H was significantly less than S at posttest and P at B3. Other cytokines and ORAC increased at B2 (548% IL-6, 514% IL-10, 15% ORAC) with no difference by treatment. Conclusion: Acute ingestion of honey and a carbohydrate sports drink before and during a soccer-simulation test did not improve performance, although honey attenuated a rise in IL-1ra. Ingestion of carbohydrate and/ or antioxidant-containing beverages at frequencies typical of a regulation match may not be beneficial for trained soccer players.